A mathematical model for evaluating accelerated wear due to inefficient maintenance - Oke, Sunday A.; Bamigbaiye, Ayokunle; Oyedokun, Oluwafemi I. (Transport, 2006)
This paper examines accelerated wear due to inefficient maintenance practice in the engineering organization, with a special focus on plant machinery. It considers some important parameters, mathematical relations and how to reduce the effect of poor maintenance practices on plant machinery. Mathematical tools of calculus, series, statistics, and variation were utilized in the development of the model. The result shows that poor maintenance practices increase accelerated wear in plant machinery while good maintenance is aided by planned maintenance, well‐stocked inventory of spare parts, good production procedures, extended plant life, etc. This work is limited in scope since it considers a limited number of parameters as measures of wear. The paper is valuable to the maintenance manager and practitioners who intend to produce/manufacture and at the same time minimize the accelerated wear in production machinery by close monitoring, and using the model as a tool. The work is of immense benefits to managers in process industries, particularly in oil and gas exploration activities. The work is new, presenting a simple approach for easy adaptation in the industry. The approach utilized is not yet documented in the maintenance engineering literature. Thus, a new area of research is opened up for research explorations for the members of the maintenance engineering community. First Published Online: 27 Oct 2010